Noninvasive Immunotyping and Immunotherapy Monitoring of Lung Cancers via Nuclear Imaging of LAG‐3 and PD‐L1 - Lishu Zhao; Jianxian Ge; Ruru Zhang; Hao Wang; Xinyue Liu; Kandi Xu; Yujin Liu; Wencheng Zhao; Wengang Zhang; Li Ye; Zhimin Chen; Jianfeng Zeng; et al. (Advanced Science)
Abstract Immunotherapy has significantly improved cancer patient survival, while its efficacy remains limited due to the reliance on a single marker like PD‐L1 as well as its spatiotemporal heterogeneity. To address this issue, combining lymphocyte activation gene‐3 (LAG‐3) with PD‐L1 is proposed for identifying immunotypes and monitoring immunotherapy through nuclear imaging. In short, 99mTc‐HYNIC‐αLAG‐3 and 99mTc‐HYNIC‐αPD‐L1 probes are synthesized using anti‐human LAG‐3 and PD‐L1 antibodies, respectively. With high radiochemical purity and in vitro stability, these probes are confirmed to specifically bind to LAG‐3 or PD‐L1 in LAG3+ A549, LAG3− A549, and H1975 cells. SPECT/CT imaging of both probes showed specific in vivo tumor uptake in multiple lung cancer models, with significant linear correlation with ex vivo tumor uptake and immunohistochemical expression levels of LAG‐3/PD‐L1. Based on this, dual‐index imaging was performed to simultaneously quantify LAG‐3 and PD‐L1. SPECT/CT imaging of 99mTc‐HYNIC‐αLAG‐3 and 125I‐αPD‐L1 successfully distinguished four immunotypes. In addition, SPECT/CT imaging revealed LAG‐3 upregulation in LLC‐bearing LAG‐3 humanized mice resistant to immunotherapy. In conclusion, this study demonstrates the feasibility of nuclear imaging of LAG‐3 and PD‐L1 for both noninvasive immunotyping and immunotherapy monitoring, thus offering novel perspectives on forecasting immunotherapy response, uncovering resistance mechanism, and optimizing combination treatment regimens.